Gambaran Nilai Elektrolit (Natrium-Kalium) Pada Penderita Dm (Diabetes Mellitus) Di Rumah Sakit Umum Wisata Universitas Indonesia Timur - Suharsi Tahir; Dinda Yuliasin Ukkas (Jurnal Media Laboran, 2020)
Diabetes mellitus is a chronic disease characterized by impaired carbohydrate, protein and fat metabolism caused by insulin deficiency. Complications that cause osmotic diuresis are electrolyte disturbances. This study describes patients with serum sodium and potassium with diabetes mellitus.The research method used is descriptive, there are 438 people with diabetes mellitus at the UIT Tourism General Hospital, both inpatient and outpatient, the samples taken are 3 people with diabetes mellitus using purposive sampling technique. Data analysis is presented in tabular form and is described and narrated. The results are sample 01 Normonatremia 137 mmol/L, Normokalemia 5.0 mmol/L, sample 02 Normonatremia 144 mml/L, Normokalemia 4.5 mmol/L, and sample 03 Normokalemia 139 mmol/L, Normokalemia 4.3 mmol/L.The conclusion of this study is that the electrolyte levels of sodium and potassium patients with diabetes mellitus at the Tourism General Hospital, Universitas Indonesia Timur are normal, because there are several factors that influence it and not all people with diabetes mellitus have electrolyte disturbances